STUDY OF IMPLEMENTATION OF DOMESTIC COMPONENT LEVEL ASSESSMENT AS A DETERMINANT ASPECT IN RANKING WINNERS OF PROCUREMENT OR TENDER FOR GAVERMENT GOODS AND SERVICES - Kanaidi, Kanaidi (Jurnal Apresiasi Ekonomi, 2023)
ABSTRACTThis study aims to answer the role of the Domestic Component Level (TKDN = Tingkat Komponen Dalam Negeri) value as a determiningaspect of the ranking of winners of government procurement/tender goods/services, and explain howthe sanctions will be if they are not followed by government goods and services procurement actors and/or goods/service providers. It is carried out using the literature review method described in the discussion, which is related to the government'sprocurement regulations for goods and services and the provisions on the value of TKDN in Presidential Decree No. 16 year 2018 jo. Presidential Decree No. 12 year 2021, Presidential Instruction No. 02 year 2022, and other related regulations. In order for the provisions for implementing TKDN to be better understood, including being well understood by business actors and the public regarding the TKDN calculation process, the verification process and the benefits of applying TKDN, it would be better if it was socialized more intensively by Public Relations employees in every institution/company/agency the government, by utilizing the means of communication and social media that are currently booming, or by increasing the number of scientific studies on this subject that are published in general through the publication of books or publication in other scientific journals. This socialization can also be carried out by inviting registered goods/services providers to take part in comprehensive training carried out by each institution/company/government agency that carries out the procurement of goods and services. Keywords: procurement of goods and services, government, calculation process, verification, level of domestic components (TKDN).Â